ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE ON COMPANY VALUE: EMPIRICAL EVIDENCE ON JAKARTA ISLAMIC INDEX 30 COMPANIES (Proceeding of SINERGY, 2026)
This research analyzes the impact of Environmental, Social, and Governance (ESG) disclosure on firm value within Sharia-compliant firms listed in the Jakarta Islamic Index 30 (JII30) over the 2023–2024 period. In response to the rising importance of sustainability considerations in investment decision-making, companies are increasingly required to provide more comprehensive non-financial disclosures as part of their accountability to stakeholders. Adopting a quantitative research approach, this study employs secondary data extracted from the annual and sustainability reports of 22 selected firms, resulting in 44 firm-year observations obtained through purposive sampling. Firm value is operationalized using the Price to Book Value (PBV) metric, while ESG disclosure levels are constructed based on indicators stipulated by the Global Reporting Initiative (GRI). The hypotheses are tested using multiple linear regression analysis after all classical assumption criteria are satisfied. The empirical results demonstrate that ESG disclosure, when evaluated collectively, has a statistically significant influence on firm value. Nevertheless, further analysis at the dimensional level reveals that environmental disclosure is negatively associated with firm value, whereas social and governance disclosures do not show significant effects. These findings indicate heterogeneous investor reactions to ESG information across different dimensions in the context of Islamic equity markets.